The interstitial compartment as a therapeutic target in heart failure - Aronson, Doron (Frontiers in Cardiovascular Medicine, 2022)
ABSTRACT Congestion is the single most important contributor to heart failure (HF) decompensation. Most of the excess volume in patients with HF resides in the interstitial compartment. Inadequate decongestion implies persistent interstitial congestion and is associated with worse outcomes. Therefore, effective interstitial decongestion represents an unmet need to improve quality of life and reduced clinical events. In this review, we provide a summary of the pathophysiology of the interstitial compartment in heart failure including dysfunction of the lymphatic system, the interstitial pressure-volume curves and the factors governing the movement of fluids between the interstitial and vascular compartments. We describe novel devices designed to directly decongest the interstitial compartment.